Cosmology with photometric redshifts - Gomes, Z (2019)
Upcoming large scale photometric surveys will require accurate photometric redshifts (photo-zs) to optimally extract astrophysical information. This thesis investigates methods of making and improving cosmological measurements using photo-zs.